PENGELOLAAN DANA DESA DALAM PENANGANAN COVID-19 DI DESA DARMASABA, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Angelina Ndatangara, Christania Rambu; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
Due to the COVID-19 pandemic, the purpose of this study was to determine the management of the Village Fund in handling COVID-19 in Darmasaba Village in the 2020 budget year. The theory used in this study is Village Financial Management according to the Regulation of the Minister of Home Affairs Number 113 of 2014, using three indicators of village financial management functions: planning, implementation, and accountability. This study used a qualitative descriptive research method. Data were obtained by observation, interviews, and documentation. The conclusions of this study are as follows: Planning begins with the refocusing of the Village Fund budget. The implementation be in the form of the establishment of posts and the monitoring activities of Darmasaba Village COVID-19 Volunteers. Accountability is directly carried out to the Regional Government. The percentage of realization of Village Fund management in handling COVID-19 in Darmasaba Village is 60,22 percent of the Village Fund.   Keywords: Management, Village Fund, COVID-19